Biology and fishery of pond smelt Hypomesus olidus in the Amur River basin - O. V. Vilkina; A. P. Shmigirilov (Известия ТИНРО)
In the Amur River, there are two ecological forms of pond smelt Hypomesus olidus: anadromous and freshwater. Generalized information about biology and fishery of the anadromous form of pond smelt is presented. The smelt migrate to the Amur for spawning in winter and spring, and for wintering in autumn. The most remote point of their spawning migration is Bolbinsky cliff (375 km from the mouth). The spawning herd is represented by three age groups: 2-, 3-, and 4-year-old fish; the two-year-old fish are the most numerous. The sex ratio of spawning smelt is close to 1 : 1, though females prevail slightly. Body length of the pubescent fish ranges from year to year from 7.6 to 13.2 cm, body weight — from 3.05 to 16.04 g; females are slightly larger than males. Absolute fecundity of pond smelt ranges from 0.7 to 12.4 thousand eggs, relative fecundity — from 199 to 1287 eggs/g. During migration to the spawning grounds, the smelt practically do not feed, but they go to active feeding after spawning. Pond smelt is a popular object of fishery in the Amur basin: on average 1569.2 t were caught annually in 2010–2019, during the spawning migration, mainly in the lower Amur River between Nikolayevsk-on-Amur and Bogorodskoe.